Fine mapping of QYrsv.swust-1BL for resistance to stripe rust in durum wheat Svevo - Zhou, Xinli; Jia, Guoyun; Luo, Yuqi; Li, Xin; Cai, Lin; Chen, Xianming; Kang, Zhensheng (Frontiers in Plant Science, 2024)
Stripe rust, caused by Puccinia striiformis f. sp. tritici (Pst), is a serious disease in wheat worldwide. There is a great need to develop cultivars with combinations of all stage resistance (ASR) and adult-plant resistance (APR) genes for sustainable control of the disease. QYrsv.swust-1BL in Italian durum wheat (Triticum turgidum ssp. durum) cultivar Svevo is effective against Pst races in China and Israel, and the gene has been previously mapped to the long arm of chromosome 1B. The gene flanked by SNP (single nucleotide polymorphism) markers IWB5732 and IWB4839 (0.75 cM). In the present study, we used high-density 660K SNP array genotyping and the phenotypes of 137 recombinant inbred lines (RILs) to fine map the QYrsv.swust-1BL locus within a 1.066 Mb region in durum wheat Svevo (RefSeq Rel. 1.0) on chromosome arm 1BL.The identified 1.066 Mb region was overlaps with a previously described map of Yr29/QYr.ucw-1BL, a stripe rust APR gene. Twenty five candidate genes for QYrsv.swut-1BL were identified through comparing polymorphic genes within the 1.066 Mb region in the resistant cultivar. SNP markers were selected and converted to Kompetitive allele-specific polymerase chain reaction (KASP) markers. Five KASP marker based on SNP was validated in a F2 and F2:3 breeding population, providing further compelling evidence for the significant effects of QYrsv.swut-1BL. These marker should be useful in marker-assisted selection for incorporating Yr29/QYrsv.swust-1BL into new durum and common wheat cultivars for resistance to stripe rust.